2021
DOI: 10.1101/2021.06.07.21257302
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic and environmental determinants of diastolic heart function

Abstract: Diastole is the sequence of physiological events that occur in the heart during ventricular filling and principally depends on myocardial relaxation and chamber stiffness. Abnormal diastolic function is related to many cardiovascular disease processes and is predictive of health outcomes, but its genetic architecture is largely unknown. Here, we use machine learning cardiac motion analysis to measure diastolic functional traits in 39,559 participants of UK Biobank and perform a genome-wide association study. W… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…All analyses in this study can be found here https://github.com/ImperialCollegeLondon/diastolic_genetics/ 43 and were conducted with R version > 3.6.0.…”
Section: Methodsmentioning
confidence: 99%
“…All analyses in this study can be found here https://github.com/ImperialCollegeLondon/diastolic_genetics/ 43 and were conducted with R version > 3.6.0.…”
Section: Methodsmentioning
confidence: 99%
“…13 Diastolic function, which is a key feature of the ageing heart, was assessed using motion analysis to derive end diastolic strain rates. 6 We assessed diffuse myocardial fibrosis, an early feature of natural ageing, 14 using native T1 mapping of the interventricular septum. 15 Central vascular function was assessed by measuring aortic distensibility from central blood pressure estimates and dynamic aortic imaging.…”
Section: Image Phenotypingmentioning
confidence: 99%
“…5 A final common pathway of cardiovascular ageing is loss of tissue compliance which is manifest through diastolic dysfunction, interstitial fibrosis and vascular remodelling. 6,7 Such changes can be assessed though non-invasive imaging and enable an estimate of how an individual's cardiovascular system has aged relative to a normative population. 8 An equivalent calculation of "age gap" has been shown to be a promising neuro-imaging marker for modelling dynamic lifespan trajectories of brain ageing.…”
Section: Introductionmentioning
confidence: 99%
“…Thickness of the IVS was calculated as the mean wall thickness of segments 2, 3, 8, 9 and 14, while PWT was taken as the mean of segments 5,6, 11, 12, and 16. To compute longitudinal and radial peak diastolic strain rates, non-rigid image co-registration was performed between successive frames to enable dynamic motion tracking of the heart during the cardiac cycle 26 . Unindexed CMR metrics were used in all subsequent analyses as discussed above.…”
Section: Methodsmentioning
confidence: 99%